Overview of Self-Compassion on Nurses at Santa Elisabeth Hospital Medan 2022 - Imelda Derang; Maria Pujiastuti; Betty Rosefa Sinaga (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Self-compassion is a mindset of accepting, understanding, and loving oneself in order to be capable of manipulating feelings positively, overcoming problems faced, decreasing anxiety, stress, and depression; and also being superb in knowing oneself when experiencing difficulties so as no longer to criticize oneself excessively and can enhance the exceptional of life, accordingly self-compassion is needed in nursing services in enhancing the excellent of nursing services. This study aims to identify self-compassion in nurses at Santa Elisabeth Hospital Medan in 2022. We used a descriptive method. The sampling technique is total sampling, and we have 196 respondents. This study uses a compassion scale questionnaire with 26 statements, consisting of 6 components, namely self-kindness, self-judgment, common humanity, isolation, mindfulness, and overidentification. The results obtained from the description of self-compassion of nurses at Santa Elisabeth Hospital Medan 2022. We found that in high category as many as 62.8%, and in low category as many as 37.2%. It can be said that the self-compassion of nurses at Santa Elisabeth Hospital Medan is high in treating themselves and others well and being able to understand one's shortcomings. We hope that nurses can maintain their self-compassion in service tasks.